Efficiency study of computation parallelization for viscous incompressible flow simulation on computing systems with shared memory by the LS-STAG method - Marchevsky, I.K.; Puzikova, V.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2015)
The LS-STAG_ext parallel software package is developed for viscous incompressible flow simulation by the LS-STAG immersed boundary method and its modifications. This package allows one to simulate a flow around moving airfoils of arbitrary shape or around airfoil systems with one or two degrees of freedom. The LS-STAG_ext package supports Intel (R) Cilk (TM) Plus, Intel (R) Threading Building Blocks, and OpenMP parallel programming technologies. The efficiency comparison of parallel algorithms implemented in the LS-STAG_ext package LS-STAG_ext with similar software tools implemented in Intel (R) Math Kernel Library is discussed. In addition, the implementation features of the FGMRES method for solving systems of linear algebraic equations are described.